Bending fatigue life enhancement of NiTi alloy by pre-strain warm surface mechanical attrition treatment. (November 2022) - Wei, Pengbo; Hua, Peng; Xia, Minglu; Yan, Kai; Lin, Hongyang; Yi, Shenghui; Lu, Jian; Ren, Fuzeng; Sun, Qingping
Abstract: Many structures like medical stents made of superelastic NiTi shape memory alloy (SMA) are subjected to cyclic bending loads and show a limited fatigue life due to crack nucleation and growth in the surface layers under local tensile stress. Here, we enhance the bending fatigue life of NiTi plates by pre-strain warm surface mechanical attrition treatment (pw-SMAT) where the austenite phase is directly subjected to severe plastic deformation and grain refinement without inducing phase transformation. Amorphous and grain size gradient (5–100 nm) microstructures, as well as a maximum compressive residual stress of 1093 MPa are produced in the surface layer of the NiTi plates via the pw-SMAT. The compressive residual stress notably reduces the surface tensile stress from bending. The grain size gradient layers with improved hardness and reduced hysteresis have high fatigue crack nucleation resistance, while the middle large-grained layers of the plates have high fatigue crack growth resistance. The combined effects of the gradient nanostructure and the compressive residual stress substantially increase the bending fatigue life of the NiTi plates from an original 10 3 cycles to over 1.3 × 10 4 cycles. The results open up a new route to improve the bending fatigue life of NiTi plates by heterogenous nanostructures. Graphical abstract: Image, graphical abstract